Las medidas sustitutivas de prisión para disminuir el hacinamiento en los centros de rehabilitación social en el Ecuador - Zambrano Parraga, María Elisa (2014)
The first chapter correspondsto the general introduction. She raises the justification and the problem of research, as well as theobjectives, hypothesis and methodology in the second chapter or theoretical framework are considered some básica spects of these areas of knowledge. Emphasis in the criminal law. It is explained in a timely manner it sobjective, as well as weekends and classicj ustifications of punishment. In addition, they clarify concepts, historical origins and evolution of the deprivation of liberty, as well as theadvantages of thesentencing. The third chapter highlights the methodology used in this research work. Chapter IV includes analysis highlights the development of the field research with data interpretation. In chapter V and VI are the conclusions and recommendations in addition to the proposed solutionto the problem